Social protection in Bangladesh : building effective social safety nets and ladders out of poverty - Rahman, Hossain Zillur, 1951-; United Nations Development Programme (Dhaka : University Press Limited, 2014)
Contributed articles.
"United Nations Development Programme."
Includes bibliographical references and index.
GenEd
Book Finder International
Keywords: Economic assistance, Domestic -- Bangladesh; Poor -- Bangladesh; Social problems and services; Bangladesh -- Economic policy